2016
DOI: 10.1017/s1368980016000239
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity, nutritional status and morbidity in Brazilian children

Abstract: Objective: To identify the association of household food insecurity (HFI) with anthropometric status, the risk of vitamin A deficiency and anaemia, morbidities such as cough and fever, and hospitalizations for diarrhoea and pneumonia in children under 5 years old. Design: Cross-sectional study using data from the 2006 Brazilian Demographic and Health Survey. HFI was measured with the Brazilian Food Insecurity Measurement Scale (EBIA). Vitamin A deficiency and anaemia were assessed in blood samples. Child morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 42 publications
6
36
1
10
Order By: Relevance
“…As reported in other studies 28,29 , the indicator of food insecurity also showed a significant correlation with the height of the children, which place children living in food insecurity conditions at greater risk of having low height for age, possibly as a consequence of a process of chronic malnutrition, even if in moderate severity. Despite the high prevalence of children exposed to some level of food insecurity, we could not find an association between food insecurity and BMI, which is comparable to the findings by Gubert et al 30 in a sample representative of Brazil. Overall, the results reflect the conditions of low human development and social exclusion in which the population of Maranhão lives 14,15 , bringing about the intimate relationship between environment conditions experienced by the child and their nutritional status.…”
Section: Discussonsupporting
confidence: 81%
“…As reported in other studies 28,29 , the indicator of food insecurity also showed a significant correlation with the height of the children, which place children living in food insecurity conditions at greater risk of having low height for age, possibly as a consequence of a process of chronic malnutrition, even if in moderate severity. Despite the high prevalence of children exposed to some level of food insecurity, we could not find an association between food insecurity and BMI, which is comparable to the findings by Gubert et al 30 in a sample representative of Brazil. Overall, the results reflect the conditions of low human development and social exclusion in which the population of Maranhão lives 14,15 , bringing about the intimate relationship between environment conditions experienced by the child and their nutritional status.…”
Section: Discussonsupporting
confidence: 81%
“…1). A total of nineteen studies met the inclusion criteria to be included in the pooled analysis (13)(14)(15)(16)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . Among these (58) describing the systematic literature search and selection of studies on food insecurity and anaemia risk Fischer et al…”
Section: Resultsmentioning
confidence: 99%
“…(2015) (27) ; Vietnam Food insecurity and anaemia risk nineteen studies, seventeen used a cross-sectional approach (14,15,16,(20)(21)(22)(23)(24)(26)(27)(28)(29)(30)(31)(32)(33)(34) , whereas the other two were longitudinal studies (13,25) . The risk ratios of 95 993 individuals in these studies were pooled for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil beberapa studi di berbagai negara menyebutkan bahwa tingkat ketahanan pangan suatu rumah tangga berkaitan erat dengan status gizi pada balita berdasarkan indikator antropometri underweight (BB/U), stunting (TB/U, dan wasting (BB/TB). [60][61][62] Hubungan antara ketahanan pangan rumah tangga dengan status gizi dalam penelitian ini menunjukkan bahwa rumah tangga tahan pangan lebih mampu dan menyediakan makanan yang beragam untuk anak-anak mereka sehingga tercapai status gizi optimal. Rumah tangga yang rawan pangan cenderung memberi makanan yang padat energi dan kekurangan zat gizi mikro sehingga berdampak pada kekurangan gizi pada anak.…”
Section: Hasil Dan Pembahasanunclassified